2022
DOI: 10.33369/pendipa.6.2.428-433
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Miskonsepsi Siswa SMP pada Konsep Getaran dan Gelombang

Abstract: This research was motivated by the result of the 2018/2019 national examination at junior high school in Serang District on the concepts of wave, electricity, and magnetism which obtained low scores. The aim of this studi was to determine how the misconceptions of Junior High School students on the concept of vibrations and waves using the four tiers test. This research was conducted at SMP of Serang District. The research method was a mixed method with a sequential explanatory design, and the sample in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…One of the most important areas of science and technology is physics (Utami et al, 2023). Physical science plays a role in the development of sciences and technologies that help people live a better life (Haerunnisa et al, 2022). Knowledge is an important thing that focuses on problems.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important areas of science and technology is physics (Utami et al, 2023). Physical science plays a role in the development of sciences and technologies that help people live a better life (Haerunnisa et al, 2022). Knowledge is an important thing that focuses on problems.…”
Section: Introductionmentioning
confidence: 99%
“…If students do not understand the basic concepts, it is likely that students will have difficulty understanding a more complex concept (Ulandari et al 2022;Sarini & Selamet 2022). So educators need to overcome this so that it does not have a negative impact on student learning outcomes (Haerunnisa et al 2022;Mellu & Baok 2020). educators must have competence and better understanding to avoid students from misunderstandings and develop appropriate instruments in identifying student misunderstandings.…”
Section: Introductionmentioning
confidence: 99%
“…The abstract characteristics of the material are one reason why this material is difficult for students to learn (Purwaningsih, 2015). In previous research, it was found that students experienced misconceptions and difficulties in solving problems related to vibration and wave material (Astuti et al, 2020;Haliza & Hadi, 2022;Haerunnisa et al, 2022). Therefore, the content of vibration and wave material has to be presented more varied and interactive in the form of text, images, audio, animation, video, quizzes, simulations, e-worksheets, digital games, and also automatic assessments.…”
Section: Introductionmentioning
confidence: 99%